Storage Stability of Spray- and Freeze-Dried Chitosan-Based Pickering Emulsions Containing Roasted Coffee Oil: Color Evaluation, Lipid Oxidation, and Volatile Compounds - Ribeiro, Elisa Franco [UNESP]; Polachini, Tiago Carregari [UNESP]; Locali-Pereira, Adilson Roberto [UNESP]; Janzantti, Natália Soares [UNESP]; Quiles, Amparo; Hernando, Isabel; Nicoletti, Vânia Regina [UNESP] (MDPI, 2023)
Drying Pickering o/w emulsions has been considered as a promising strategy to produce oil microcapsules, as long as their quality parameters can be preserved over storage. In this sense, it is shown as an interesting alternative to preserve the quality of roasted coffee oil, a valuable agroindustrial byproduct. Thus, freeze- and spray-dried chitosan-based Pickering emulsions of roasted coffee oil were evaluated over 30 days of storage at 25 °C together with the non-encapsulated oil as a control. Water sorption isotherms were determined, whereas color, oxidative stability (peroxide value and conjugated dienes) and volatile compounds were assessed over the storage period. Type II isotherms and Guggenheim–Anderson–Boer (GAB) model parameters showed that water binding was impaired by the surface oil in freeze-dried samples. Oxidation was maintained under acceptable values over the storage for all samples, with slightly higher protection also observed for volatile compounds in the spray-dried particles. The powdered emulsions were able to suitably preserve the oil’s quality over 30 days of storage, enabling its commercialization and application as a food ingredient and potential flavoring.
Keywords: drying; lipid oxidation; self-aggregation; sorption isotherms; volatile compounds